Rapid, Simultaneous Detection of Clostridium sordellii and Clostridium perfringens in Archived Tissues by a Novel PCR-Based Microsphere Assay: Diagnostic Implications for Pregnancy-Associated Toxic Shock Syndrome Cases - Julu Bhatnagar; Marlene DeLeon-Carnes; Kathryn L. Kellar; Kakali Bandyopadhyay; Zoi-Anna Antoniadou; Wun-Ju Shieh; Christopher D. Paddock; Sherif R. Zaki (Hindawi Limited, 2012)
Clostridium sordellii and Clostridium perfringens are infrequent human pathogens; however, the case-fatality rates for the infections are very high, particularly in obstetric C. sordellii infections (>90%). Deaths from Clostridium sordellii and Clostridium perfringens toxic shock (CTS) are sudden, and diagnosis is often challenging. Formalin-fixed, paraffin-embedded (FFPE) tissues usually are the only specimens available for sudden fatal cases, and immunohistochemistry (IHC) for Clostridia is generally performed but it cannot identify species. A clear need exists for a rapid, species-specific diagnostic assay for FFPE tissues. We developed a duplex PCR-based microsphere assay for simultaneous detection of C. sordellii and C. perfringens and evaluated DNA extracted from 42 Clostridium isolates and FFPE tissues of 28 patients with toxic shock/endometritis (20 CTS, 8 non-CTS, as confirmed by PCR and sequencing). The microsphere assay correctly identified C. sordellii and C. perfringens in all known isolates and in all CTS patients (10 C. sordellii, 8 C. perfringens, 2 both) and showed 100% concordance with PCR and sequencing results. The microsphere assay is a rapid, specific, and cost-effective method for the diagnosis of CTS and offers the advantage of simultaneous testing for C. sordellii and C. perfringens in FFPE tissues using a limited amount of DNA.